Skip to content
Related Articles

Related Articles

Improve Article

Class 10 RD Sharma Solutions – Chapter 3 Pair of Linear Equations in Two Variables – Exercise 3.4 | Set 1

  • Last Updated : 30 Apr, 2021
Geek Week

Solve each of the following systems of equations by the method of cross multiplication.

Question 1. x + 2y + 1 = 0 and 2x – 3y – 12 = 0 

Solution:

Given that,

x + 2y + 1 = 0

2x – 3y – 12 = 0

On comparing both the equation with the geneal form we get



 a1 = 1, b1 = 2, c1 = 1, a2 = 2, b2 = −3, c2 = -12

Now by using cross multiplication we get

x/(b1c2 – b2c1) = y/(c1a2 – c2a1) = 1/(a1b2 – a2b1)

x/(-24 – (-3)) = y/(-2 – (-12)) = 1/(-3 – 4)

x/(-24 + 32) = y/(2 + 12) = 1/ (-3 – 4)

x = -21/-7

So, x = 3

and 



y = 14/-7

y = -2

Hence, x = 3 and y = -2

Question 2. 3x + 2y + 25 = 0 and 2x + y + 10 = 0

Solution:

Given that,

3x +2y + 250

2x + y + 10 = 0

On comparing both the equation with the geneal form we get

 a1 = 3, b1 = 2, c1 = 25, a2 = 2, b2 = 1, c2 = 10

Now by using cross multiplication we get

x/(b1c2 – b2c1) = y/(c1a2 – c2a1) = 1/(a1b2 – a2b1)

x/(20 – 25) = y/(50 – 30) = 1/(3 – 4)

x/-5 = y/20 = 1/-1

x = -5 × (-1) 

x = 5

x = -5 × (-1) = 5

y/20 = -1

y = 20 × (-1) = −20

Hence, x = 5y and y = −2

Question 3. 2x + y = 35 and 3x + 4y = 65

Solution:



Given that,

2x + y = 35

3x + 4y = 65

Or 2x + y – 35 = 0

3x + 4y – 65 = 0

On comparing both the equation with the geneal form we get

 a1 = 2, b1 = 1, c1 = -35, a2 = 3, b2 = 4, c2 = -65

Now by using cross multiplication we get

x/(b1c2 – b2c1) = y/(c1a2 – c2a1) = 1/(a1b2 – a2b1)

x/(-65 – (-140)) = y/(-105-(-65 × 2)) = 1/( 8 – 3)

x/(-65 + 140) = y/( -105 + 130) = 1/5

x = 75/5

x = 15

y = 25/5

y = 5

Hence, x = 15 and y = 5

Question 4. 2x – y = 6 and x – y = 2

Solution:

Given that,

2x – y = 6

x – y = 2

Or 2x – y – 6 = 0

x – y – 2 = 0

On comparing both the equation with the geneal form we get

 a1 = 2, b1 = -1, c1 = -6, a2 = 1, b2 = -1, c2 = -2

Now by using cross multiplication we get

x/(b1c2 – b2c1) = y/(c1a2 – c2a1) = 1/(a1b2 – a2b1)

x/(2 – 6) = y/(-6 + 4) = 1/(-2 + 1)

So, x = 4

and y = 2

Hence, x = 4 and y = 2



Question 5. (x + y)/xy = 2 and (x − y)/xy = 6

Solution:

Given that,

(x + y)/xy = 2,

(x − y)/xy = 6

Or, 1/x + 1/y – 2 = 0

and,

1/x – 1/y – 6 = 0

On comparing both the equation with the geneal form we get

 a1 = 1, b1 = 1, c1 = -2, a2 = 1, b2 = -1, c2 = -6

Now by using cross multiplication we get

x/(b1c2 – b2c1) = y/(c1a2 – c2a1) = 1/(a1b2 – a2b1)

(1/x)/(-6 + 2) = (1/y)/(2 + 6) = 1/(1 + 1)

So, x = -1/2

and y = 1/4

Hence, x = -1/2 and y = 1/4

Question 6. ax + by = a – b and bx – ay = a + b

Solution:

Given that,

ax + by = a – b

bx – ay = a + b

Or, ax + by – (a – b) = 0

bx – ay – (a + b) = 0

On comparing both the equation with the geneal form we get

 a1 = a, b1 = b, c1 = -(a – b), a2 = b, b2 = -a, c2 = (a + b)

Now by using cross multiplication we get

x/(b1c2 – b2c1) = y/(c1a2 – c2a1) = 1/(a1b2 – a2b1)

x/(−b(a + b) − (-a)(-(a − b))) = y/((-(a − b) × b) – (-(a + b) × a) = 1/ (-a2 – b2)

x/(-ab – b2 – a2 + ab) = y/(-ab – b2 + a2 + ab) = 1/-(-a2 + b2)

So, 

x/-(-a2 + b2) = 1/-(-a2 + b2

x = 1



and, y/(a2 + b2) = 1/-(-a2 + b2)

y = -1

Hence, x = 1 and y = -1

Question 7. x + ay = b and ax – by = c

Solution:

Given that,

x + ay = b

ax – by = c

Or, x + ay – b = 0

ax – by – c = 0

On comparing both the equation with the geneal form we get

a1 = 1, b1 = a, c1 = – b, a2 = a, b2 = -b, c2 = -c

Now by using cross multiplication we get

x/(b1c2 – b2c1) = y/(c1a2 – c2a1) = 1/(a1b2 – a2b1)

x/(-ac – b2) = y/(-ab + c) = 1/(-b – a2)

x/(- ac – b2) = 1/(-b – a2

x = (ac + b2)/(a2 + b)

and,

y/(- ab + c) = 1/(-b – a2)

y =(ab – c)/(a2 + b)

Hence, x = (ac + b2)/(a2 +b) and y =(ab – c)/(a2 + b)

Question 8. ax + by = a2 and bx + ay = b2

Solution:

Given that,

ax + by = a2

bx + ay = b2

Or, ax + by – a2 = 0

bx + ay – b2 = 0

On comparing both the equation with the geneal form we get

a1 = a, b1 = b, c1 = – a2, a2 = b, b2 = a, c2 = -b2

Now by using cross multiplication we get

x/(b1c2 – b2c1) = y/(c1a2 – c2a1) = 1/(a1b2 – a2b1)

x/(-b3 + a3) = y/(-a2b + ab2) = 1/(a2 – b2)

x/(a3 – b3) = y/(-ab(a – b)) = 1/(a2 – b2)

x= (a3 – b3)/(a2 – b2)

x = ((a – b)(a2 + ab + b2))/(a + b)(a – b)

x = (a2 + ab + b2)/a + b

and,

y/(-ab(a – b)) = 1/(a2 – b2)

(a – b)(a2 + ab + b2) (a + ba – b)

 y = -ab(a – b)/(a + b)(a – b)

y= -ab/(a + b)



Hence, x = (a2 + ab + b2)/(a + b) and y = -ab/(a + b)

Question 9. (5/(x + y)) – (2/(x – y)) = -1 and (15/(x + y)) + (7/(x – y)) = 10

Solution:

Given that,

(5/(x + y)) – (2/(x – y)) = -1

(15/(x + y)) + (7/(x – y)) = 10

Let, us assume

x + y = a, and x – y = b, then

(5/a) – (2/b) + 1 = 0

(15/a) – (7/b) + 10 = 0

On comparing both the equation with the geneal form we get

a1 = 5, b1 = -2, c1 = – 1, a2 = 15, b2 = 7, c2 = -10

Now by using cross multiplication we get

x/(b1c2 – b2c1) = y/(c1a2 – c2a1) = 1/(a1b2 – a2b1)

((1/a)/(20 – 7)) = ((1/b)(15 + 50)) = 1/(35 + 30)

((1/a)/13) = ((1/b)/65) = 1/65

So,

1/a = 13/65

a = 5

and,

1/b = 65/65

b =1

= x + y = 5……       (1)

= x – y = 1…..      (2)

Now, by adding eq(1) and (2) then we get,

x = 3 and y = 2

Hence, x = 3 and y = 2

Question 10. (2/x) + (3/y) = 13 and (5/x) – (4/y) = -2

Solution:

Given that,

(2/x) +(3/y) = 13

(5/x) – (4/y) = -2

Or, (2/x) + (3/y) – 13 = 0

(5/x) – (4/y) + 2 = 0

On comparing both the equation with the geneal form we get

a1 = 2, b1 = 3, c1 = – 13, a2 = 5, b2 = -4, c2 = 2

Now by using cross multiplication we get

x/(b1c2 – b2c1) = y/(c1a2 – c2a1) = 1/(a1b2 – a2b1)

 = ((1/x)/(6 – 52)) = ((1/y)(-65 – 4)) = 1/(-8 – 5)

= ((1/x)/-46) = ((1/y)/(-69)) = 1/(-23)

Now,

1/x = -46/(-23)

x = 1/2

and,

1/y = -69/-23

y = 1/3

Hence, x = 1/2 and y = 1/3

Question 11. (11x + y)) + (6/(x – y)) = 5 and (38/(x + y)) + (21(x – y)) = 9

Solution:

Given that,

(57/(x + y)) + (6/(x – y)) = 5

(38/(x + y)) + (21(x – y)) = 9

Let us considered

x + y = p

x – y = q

So,

(57/p) + (6/q) – 5 = 0

(38/p) + (21/q) – 9 = 0

On comparing both the equation with the geneal form we get

a1 = 57, b1 = 6, c1 = – 5, a2 = 38, b2 = 21, c2 = -9

Now by using cross multiplication we get

x/(b1c2 – b2c1) = y/(c1a2 – c2a1) = 1/(a1b2 – a2b1)

((1/p)/(-54 + 105)) = ((1/q)/(-190 + 513)) = 1/(1197 – 228)



((1/p)/51) = ((1/q)/323) = 1/969

So,

((1/p)/51) = 1/969

1/p = 51/969

p = 19

and,

((1/q)/323) = 1/969

1/q = 323/969

q = 3

Now, adding eq x + y = 19 and x – y = 3 then we get:

x = 11 and y = 8

Hence, x = 11 and y = 8

Question 12. (x/a) + (y/b) = 2 and ax – by =  a2 – b2

Solution:

Given that,

(x/a) + (y/b) = 2

ax – by = a2 – b2

(x/a) + (y/b) – 2 = 0

ax – by – (a2 – b2) = 0

On comparing both the equation with the geneal form we get

a1 = 1/a, b1 = 1/b, c1 = – 2, a2 = a, b2 = -b, c2 = -(a2 – b2)

Now by using cross multiplication we get

x/(b1c2 – b2c1) = y/(c1a2 – c2a1) = 1/(a1b2 – a2b1)

x/((-1/b)(a2 + b2)-2b) = y/((-2a) + (1/a)(a2 – b2)) = 1/((-b/a) – (a/b))

x/((-a2/b) – b) = y/(-a – (b2/a)) = 1/-(a2 + b2)/ab

x/(-(a2 + b2)/b) = y/(-(a2 + b2)/a)) = 1/-(a2 + b2)/ab

So,

 x/(-(a2 + b2)/b) = 1/-( a2 + b2)/ab

x = -(a2 + b2)ab/-b(a2 + b2

x = a

and,

 y/(-(a2 + b2)/a)) = 1/-(a2 + b2)/ab

y = -(a2 + b2)ab/-a(a2 + b2

y = b

Hence, x = a and y = b

Question 13. (x/a) + (y/b) = a + b and (x/a2) + (y/b2) = 2

Solution:

Given that,

(x/a) + (y/b) = a + b

(x/a2) + (y/b2) = 2

(x/a) + (y/b) – a + b = 0

(x/a2) + (y/b2) – 2 = 0

On comparing both the equation with the geneal form we get

a1 = 1/a, b1 = 1/b, c1 = -(a + b), a2 = 1/ a2, b2 = 1/ b2, c2 = -2

Now by using cross multiplication we get

x/(b1c2 – b2c1) = y/(c1a2 – c2a1) = 1/(a1b2 – a2b1)

(x/ (-2/b) + (a/b2) + (1/b)) = (-y/(-2/a) + (1/a) + (b/ a2)) = (1/(-1/ ab2) – (-1/ a2b))

Now,

x/((a – b)b2) = 1/(-1/ab2) – (-1/a2b)

x = a2

and,

-y/((-a – b)/a2) + (1/a) + (b/b2) = 1/(-1/ab2) – (-1/a2b)



y = b2

Hence, x = a2 and y = b2

Question 14. x/a = y/b and ax + by = a2 + b2

Solution:

Given that,

x/a = y/b

ax + by = a2 + b2

On comparing both the equation with the geneal form we get

a1 = 1/a, b1 = 1/b, c1 = 0, a2 = a, b2 = b, c2 = -(a2 + b2)

Now by using cross multiplication we get

x/(b1c2 – b2c1) = y/(c1a2 – c2a1) = 1/(a1b2 – a2b1)

x/((a2 + b2)/b) = y/((a2 + b2)/a) = 1/((a/b) + (b/a))

Now,

x/((a2 + b2)/b) = 1/((a/b) + (b/a))

x = a

and,

 y/((a2 + b2)/a) = 1/((a/b) + (b/a))

y = b

Hence, x = a and y = b

Attention reader! All those who say programming isn’t for kids, just haven’t met the right mentors yet. Join the  Demo Class for First Step to Coding Coursespecifically designed for students of class 8 to 12. 

The students will get to learn more about the world of programming in these free classes which will definitely help them in making a wise career choice in the future.




My Personal Notes arrow_drop_up
Recommended Articles
Page :